Differential-Drive Mobile Robot Control Design based-on Linear Feedback Control Law - Siti Nurmaini; Kemala Dewi; Bambang Tutuko Tutuko (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
This paper deals with the problem of how to control differential driven mobile robot with simple control law. When mobile robot moves from one position to another to achieve a position destination,  it  always produce  some errors.  Therefore,  a  mobile robot  requires  a certain control law to drive the robot’s movement to the position destination with a smallest possible error. In this paper, in order to reduce position error, a linear feedback control is proposed with pole placement approach to regulate the polynoms desired. The presented work leads to an improved understanding of differential-drive mobile robot (DDMR)-based kinematics equation, which will assist to design of suitable controllers for DDMR movement . The result show by using the linier feedback control method with pole placement approach the position error is reduced and fast convergence is achieved.